Answer:
w = -56
Explanation:
Solve for w:
21 = (-3 w)/8
Hint: | Reverse the equality in 21 = (-3 w)/8 in order to isolate w to the left hand side.
21 = (-3 w)/8 is equivalent to (-3 w)/8 = 21:
(-3 w)/8 = 21
Hint: | Multiply both sides by a constant to simplify the equation.
Multiply both sides of (-3 w)/8 = 21 by -8/3:
(-8 (-3) w)/(3×8) = (-8)/3×21
Hint: | Express (-8)/3×(-3)/8 as a single fraction.
(-8)/3×(-3)/8 = (-8 (-3))/(3×8):
(-8 (-3))/(3×8) w = (-8)/3×21
Hint: | Express (-8)/3×21 as a single fraction.
(-8)/3×21 = (-8×21)/3:
(-8 (-3) w)/(3×8) = (-8×21)/3
Hint: | In (-8 (-3) w)/(3×8), divide -8 in the numerator by 8 in the denominator.
(-8)/8 = (8 (-1))/8 = -1:
(-3-1 w)/3 = (-8×21)/3
Hint: | In (-(-3) w)/3, divide -3 in the numerator by 3 in the denominator.
(-3)/3 = (3 (-1))/3 = -1:
--1 w = (-8×21)/3
Hint: | Multiply all instances of -1 in -(-w).
(-1)^2 = 1:
w = (-8×21)/3
Hint: | In (-8×21)/3, divide 21 in the numerator by 3 in the denominator.
21/3 = (3×7)/3 = 7:
w = -87
Hint: | Multiply -8 and 7 together.
-8×7 = -56:
Answer: w = -56